If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + -3b = -10 + -6b Solving -1 + -3b = -10 + -6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '6b' to each side of the equation. -1 + -3b + 6b = -10 + -6b + 6b Combine like terms: -3b + 6b = 3b -1 + 3b = -10 + -6b + 6b Combine like terms: -6b + 6b = 0 -1 + 3b = -10 + 0 -1 + 3b = -10 Add '1' to each side of the equation. -1 + 1 + 3b = -10 + 1 Combine like terms: -1 + 1 = 0 0 + 3b = -10 + 1 3b = -10 + 1 Combine like terms: -10 + 1 = -9 3b = -9 Divide each side by '3'. b = -3 Simplifying b = -3
| 180-2x=4 | | X^2+49=1024 | | u+12=31 | | 2x+5*7=4x+57 | | 7+5x=-13 | | 4x-2x=180 | | 5x^2+12=5x | | 3(y+6)=13 | | 6+4x=-58 | | (a+b)+2a=180 | | 1+8+x=23 | | 8.3=4k-2.4 | | x^4-4x^3+4x^2-16x=0 | | Y=8x+4.9 | | -6(3x+8)=-18x-48 | | x^4-4x^3+4x^2=16x | | 4(-2x+5)= | | 175-4p=375 | | 0=w^2-3w-1890 | | Y=10sin | | 4x+6=2x-30 | | 4k+2(5k-6)=-3-39 | | 6x-54=-24x | | 3(x-2)=5(x+8) | | 24-3k=-2k | | 6-6=8x+4x | | x^2-4xy+y^2-16=0 | | 0.15(40)+.60X=0.40(40+X) | | 65+5=40 | | 3x-7/4=4x+5/3 | | 3x-4+2x=5x-6 | | 16-(3m+3)=4+4m-19 |